The Politics of Disaster : Tracking the Impact of Hurricane Andrew - Twigg, David K. (Book collections on Project MUSE., 2012)
An examination of the politics of disaster on the local level through the analysis of three levels of incumbent politicians in the aftermath of Hurricane Andrew in South Florida.